Using the Advocacy Approach in Community Organizing to Achieve Social Justice in Kuwaiti Society - المضف، وضحة أحمد جاسم محمد (الجمعية المصرية للأخصائيين الإجتماعيين, 2020)
هدفت الدراسة الراهنة إلى تحديد استخدام مدخل المدافعة في طريقة تنظيم المجتمع لتحقيق العدالة الاجتماعية في المجتمع الكويتي، وقد أسفرت النتائج أن الجمعيات الأهلية تستخدم مدخل المدافعة لتحقيق العدالة الاجتماعية، وأفادت نتائج الدراسة إلى وجود علاقة طردية دالة إحصائيا عند مستوى معنوية (0.01) بين الأنشطة والبرامج المستخدمة في مدخل المدافعة في الجمعيات الأهلية وتحقيق العدالة الاجتماعية بالمجتمع الكويتي، وأن أكثر الأنشطة والبرامج المستخدمة في مدخل المدافعة في الجمعيات الأهلية ارتباطا بتحقيق العدالة الاجتماعية بالمجتمع الكويتي تمثلت في: الأنشطة والبرامج التدريبية والتأهيلية، ثم الأنشطة والبرامج الدفاعية، ثم الأنشطة والبرامج الثقافية ، يليها الأنشطة والبرامج التعليمية، وأخيراً الأنشطة والبرامج الاجتماعية، كما توصلت النتائج إلى أن إسهامات العدالة الاجتماعية في نجاح مدخل المدافعة في الجمعيات الأهلية بلغت معدلات مرتفعة واحتل بُعد المساواة المرتبة الأولى ثم تلاه بعد العدالة وأخيرا بعد تكافؤ الفرص، كما رصدت نتائج الدراسة أن الجمعيات الأهلية تستخدم الاستراتيجيات الأكثر تأثيرا كاستراتيجية الضغط على السلطة التشريعية لتعديل السياسات بما يتماشى مع حقوق المستفيدين، بالإضافة إلى استخدام استراتيجية التحالف من أجل كسب التأييد المجتمعي نحو قضايا المستفيدين في الجمعية، فضلاً عن استخدام استراتيجية المدافعة عن الفئات المهضومة الحق من خلال تنظيم جهودهم، كما أشارت النتائج إلى أن أهم التكتيكات التي تستخدمها الجمعيات الأهلية وتساعد في تحقيق العدالة الاجتماعية هي العمل المباشر مع المسؤولين والمتخصصين والمواطنين للوصول لحلول مشتركة لتحقيق العدالة الاجتماعية، بالإضافة إلى الاتصالات المفتوحة والمستمرة مع جميع الأطراف المعنية للمشاركة في عملية صنع واتخاذ القرار لإقرار كادر المهنيين المستفيدين لدى الجمعية، كما أسفرت النتائج أيضاً عن أهم الأدوات المستخدمة في مدخل المدافعة التي تساعد في تحقيق العدالة الاجتماعية وتمثلت في الندوات للتبادل الفكري الذي يسلط الضوء على تكافؤ الفرص لأفراد المجتمع، وكذلك مقابلة المشرعين لإصدار تشريعات جديدة أو تعديلها لتحقيق العدالة الاجتماعية بين أفراد المجتمع، كما أشارت النتائج إلى أن المعوقات التي تحد من فعالية مدخل المدافعة في الجمعيات الأهلية لتحقيق العدالة الاجتماعية هي استعجال نتائج المدافعة لتحقيق العدالة الاجتماعية، وأيضا من المعوقات التي احتلت المراتب الأولى قلة نشر الوعي المجتمعي المرتبط بأهمية المدافعة ودورها في تحقيق العدالة الاجتماعية لأفراد المجتمع، وكذلك قلة تقدير المسؤولين لأهمية الحوارات الدفاعية واستجابتهم للمشاركة فيها، وحول تحديد المقترحات التي تدعم مدخل المدافعة لتحقيق العدالة الاجتماعية في المجتمع الكويتي أفادت النتائج بضرورة نشر الوعي المجتمعي بأهمية المدافعة عن القضايا المجتمعية الملحة بما يسهم في تحقيق العدالة الاجتماعية، ومن المقترحات التي احتلت المراتب الأولى الاهتمام باستخدام وسائل الإعلام المتنوعة لنشر قضايا المدافعة لتحقيق العدالة الاجتماعية وإقامة دورات تدريبية وتأهيلية للعاملين في الجمعية في مجال المدافعة لتحقيق العدالة الاجتماعية.
The present study aimed at determining the use of the advocacy approach in the community organizing method to achieve social justice in the Kuwaiti society. The results showed that the NGOs use the advocacy approach to achieve social justice. The results of the study reported a statistically significant relationship 0.01 Among the activities and programs used in the advocacy approach in the civil societies and the achievement of social justice in the Kuwaiti society, and the most activities and programs used in the advocacy approach in the civil associations in connection with the achievement of social justice in the Kuwaiti society The activities and advocacy programs, then the activities and cultural programs, followed by the activities and educational programs, and finally the social activities and programs. The results also found that the contributions of social justice to the success of the advocacy approach in the civil associations reached high rates, Equality was first, followed by justice and finally after equality of opportunity, and the results of the study showed that NGOs use the most influential strategies such as the strategy of lobbying the legislature to amend policies, In addition to using the Alliance's strategy to build community support towards the issues of beneficiaries in the society, as well as using the strategy of advocacy the right groups by organizing their efforts. The results also pointed to the most important tactics used by NGOs and help in achieving social justice Is to work directly with officials, professionals and citizens to reach common solutions to achieve social justice, in addition to open and ongoing communication with all concerned parties to participate in the decision-making process to approve the professional cadre for the staff. The results also revealed the most important tools used in the introduction of advocacy that help in the achievement of social justice and were represented in seminars for intellectual exchange that highlight the equal opportunities of the members of society, as well as meet legislators to enact new legislation or amend them to achieve social justice among the members of society, And the results indicate that the obstacles that limit the effectiveness of the entrance of the defenders in the civil societies to achieve social justice is the urgency of the results of advocacy to achieve social justice, as well as the constraints that occupied the first rank, And the lack of appreciation of officials for the importance of advocacy dialogues and their response to participation in them, and on the identification of proposals that support the advocacy approach to achieve social justice in the Kuwaiti society. The results indicated the need to raise awareness of the importance of advocacy the pressing social issues, Contribute to the achievement of social justice, and also from the proposals that occupied the first salary was the interest in the use of various media to disseminate the issues of advocacy to achieve social justice, and the most important Proposals to establish training and rehabilitation courses for the members of the association in the field of advocacy to achieve social justice.
Keywords: علم الاجتماع -- التنظيم الاجتماعي -- العدالة الاجتماعية -- الكويت